(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Unlimited Buffet restaurants, a concept that dates back to the 16th century, are regaining popularity. Buffets remain one of the most popular alternatives for customers due to their versatility, diverse food options, and endless servings at a fair price. It is a common style of meal service at many restaurants and is regularly utilized at banquet events. This study aims to determine the significance of service quality in an unlimited buffet restaurant in Quezon City for the success or failure of this business. In line with this, the researchers would like to know how customer preferences affect service quality in this kind of food business. According to the results of the study, customers were very satisfied with the service quality, the food quality, and the place; the most common problem encountered with quality service was that buffet restaurants’ customers could not be satisfied because of time constraints. This study recommends that restaurants continually retain (grp5 4212)their ability to prepare food quickly. Customer satisfaction with the unlimited buffet would be advantageous to the business. To sustain customer satisfaction, it is recommended that the business continue to implement quality services such as service quality, food quality, and place. Researchers recommend utilizing time management to make the most of the restaurant’s allotted time in order to maintain customer satisfaction with the unlimited buffet.